Implementasi Pakan Ikan Dengan Sistem Pelontar Berbasis Sistem Tertanam - aji saputra; Selamet Samsugi; styawati styawati (Jurusan Ilmu Komputer Fakultas MIPA Universitas Lampung, 2024)
Freshwater fish farming has high appeal among the public, however the process of feeding fish is still mostly done manually using traditional methods that are less effective. This article discusses the implementation of fish feed with a throwing system based on an integrated system using an ultrasonic sensor, DC motor, and 5V relay with an Arduino Uno microcontroller. Feeding fish is an important aspect of fish farming. Currently, fish feeding methods are still mostly done manually by throwing bait by hand. These manual techniques tend to be ineffective and can result in irregular feeding. For example, using a bucket to throw food directly into a fish pond can cause the fish to eat too much without proper control. This can result in excessive feeding, additional costs, and poor air quality. Therefore, it is necessary to develop an automatic and programmed fish food throwing system to increase the efficiency and effectiveness of feeding. It is hoped that the use of ultrasonic sensors, DC motors and 5V relays with the Arduino Uno microcontroller can provide a solution to overcome this problem. The main objective of this research is to design and implement an embedded system-based fish feed launcher that can provide feed automatically with good control. This system is expected to improve fish quality, reduce additional costs, and provide convenience for fish farmers. The problem that this tool wants to solve is how to increase the efficiency and effectiveness of fish feeding in freshwater fish farming. Currently, feeding is still done manually, and uncontrolled feeding frequency can result in problems such as excessive feeding and poor air quality. The implementation of a throwing system based on an embedded system with an ultrasonic sensor is expected to be able to overcome this problem by providing feed automatically and programmed. Thus, this research aims to create innovative solutions in fish feeding that can increase production efficiency and the welfare of fish farmers.